Application of Technological Control Measures on Vehicle Pollution: A Cost-Benefit Analysis in China - Paulo Augusto Nunes; Qiang Wu (Fondazione Eni Enrico Mattei (FEEM), 2005)
For the past two decades, China has experienced strong, continuous economic growth. At the same time, the number of motor vehicles in China has rapidly increased. As a direct result of such a phenomenon, China has been registering significant increases in air pollution. In spite of recent advances in air pollution control, it remains a serious problem for Chinas major cities, and constitutes an important issue in the agenda of its policy makers. The object of this paper is to explore the use of cost-benefit analysis (CBA) to evaluate and rank alternative policy scenarios regarding the control of air pollution emitted by motor vehicles. The empirical analysis carried out relates specifically to the Chinese context, over a twenty year period, from 2001 to 2020, and focuses on emission changes of the following three principal pollutants: CO, HC and NOx.
Keywords: O33; O53; 330; Vehicle; Pollution; CO; HC; NOx; Scenario; Standard; Cost; Benefit; China; Luftreinhaltung; Verkehrsökologie; Kosten-Nutzen-Analyse; China